Respuestas
Respuesta:
Explicación paso a paso:
13) √91 + ( 5+ 11 - 13) ²
√91 + 3 ²
√91 + 9
√100 = 10
14) √(3+8-9) × 2²
√2×2²
√2 ³
2√2
15) √100 + ³√8 - ³√1
10 √10 + 2 - 1
10 √10 + 1
16) √10 + √44 - 2³
√10 +√44 - 8
√10 + √36
√10+ 6
√16 = 4
17) √144 + ³√27 - ⁵√1
12 + 3 - 1
14
18) √(4+16)² - (20-8)²
√ 20² - 12²
√(20-12)× (20+12)
√8 × 32
√256 = 16
19) √68 - √19 - √7 + √4
√68- √19 - √7 + 2
√68 - √19 - √9
√68 - √ 19 - 3
√68- 4
√64 = 8
20) √1 +√5+ √7+ √81
√1 + √ 5+ √ 7 + 9
√1 + √5 + √16
√1 + √ 5 + √ 16
√1+ √ 5 + 4
√1+ √9
√1+3
√4 = 2